Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen Jasa Transportasi Gojek Online di Kota Ambon - Imran Hatala (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2024)
The ability of a transportation service company, namely Gojek online, to be able to recognize, meet and satisfy customer needs well, is a strategy for every company. This research was conducted to find out empirical evidence of the influence of price and service quality on online Gojek customer satisfaction in Ambon City. The research sample was obtained from 50 respondents and taken by incidental sampling, which is a sampling technique based on coincidence/indental. The data collection technique uses a questionnaire. The data analysis technique in this study uses multiple regression analysis with the program used is SPSS version 17. The results of this study show that there is a positive and significant influence between service quality and customer satisfaction can be accepted. There is a positive and significant influence of price on acceptable consumer satisfaction. Service quality is the variable that most affects Gojek online consumer satisfaction